Sex is no determinant of cardioprotection by ischemic preconditioning in rats, but ischemic/reperfused tissue mass is for remote ischemic preconditioning - Lieder, Helmut R. (Physiol Rep, 2019)
We determined the impact of sex on the magnitude of cardioprotection by local and remote ischemic preconditioning (IPC and RIPC) and of ischemic/reperfused peripheral tissue mass on protection by RIPC. Hearts of female and male Lewis rats were excised, perfused with buffer, and underwent either IPC by 3 × 5/5 min global zero‐flow ischemia/reperfusion (GI/R) or time‐matched perfusion (TP) before 30/120 min GI/R. In a second approach, anesthetized female and male Lewis rats underwent RIPC, 3 × 5/5 min ischemia/reperfusion of one or both hindlimbs (1‐RIPC or 2‐RIPC), or placebo. Thirty minutes after the RIPC/placebo protocol, hearts were excised and subjected to GI/R. In female and male hearts, infarct size was less with IPC than with TP before GI/R (IPC+GI/R(female): 12 ± 5%; IPC+GI/R(male): 12 ± 7% vs. TP+GI/R(female): 33 ± 5%; TP+GI/R(male): 37 ± 7%, P < 0.001). With 2‐RIPC, infarct size was less than with 1‐RIPC in female and male rat hearts, respectively (2‐RIPC+GI/R(female): 15 ± 5% vs. 1‐RIPC+GI/R(female): 22 ± 7%, P = 0.026 and 2‐RIPC+GI/R(male): 16 ± 5% vs. 1‐RIPC+GI/R(male): 22 ± 8%, P = 0.016). Infarct size after the placebo protocol and GI/R was not different between female and male hearts (36 ± 8% vs. 34 ± 5%). Sex is no determinant of IPC‐ and RIPC‐induced cardioprotection in isolated Lewis rat hearts. RIPC‐induced cardioprotection is greater with greater mass of ischemic/reperfused peripheral tissue.